Structural mechanics fundamentals - Carpinteri, A. (Boca Raton : CRC Press, Taylor & Francis Group, 2014)
'This book gives you a complete and uniform treatment of the most fundamental and essential topics in structural mechanics. Presenting a traditional subject in an updated and modernized way, this book merges classical topics with ones that have taken shape in more recent times, such as duality:geometry of areaskinematics and statics of rigid body systemsdetermination of constraint reactionsinternal beam reactionsstatically determinate beam systemsanalysis of strain and stresstheory of elasticitythe Saint Venant problembeams and plates in flexurestatically indeterminate beam systems: method of forcesenergy methods for the solution of beam systems.It can be used as a text for final year undergraduate or graduate students in structural engineering or even by some architecture students and also serves as a useful reference for practising engineers and researchers'--
Includes bibliographical references and index.
Keywords: Structural engineering